1998
DOI: 10.1007/bf02845552
|View full text |Cite
|
Sign up to set email alerts
|

Schwarzschild black hole with global monopole charge

Abstract: We derive the metric for a Schwarzschild black hole with global monopole charge by relaxing asymptotic flatness of the Schwarzschild field. We then study the effect of global monopole charge on particle orbits and the Hawking radiation. It turns out that existence, boundedness and stability of circular orbits scale up by (1 − 8πη 2 ) −1 , and the perihelion shift and the light bending by (1 − 8πη 2 ) −3/2 , while the Hawking temperature scales down by (1 − 8πη 2 ) 2 the Schwarzschild values. Here η is the glob… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
71
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(73 citation statements)
references
References 7 publications
(7 reference statements)
1
71
0
Order By: Relevance
“…Dadhich et al derived the metric of a Schwarzschild black hole with global monopole charge by relaxing asymptotic flatness and investigated several astrophysical aspects [17]. However, in the presence of the cosmological constant, the metric coefficients of this geometry become modify as follows [18]:…”
Section: Spherically Symmetric Metrics With Horizonsmentioning
confidence: 99%
“…Dadhich et al derived the metric of a Schwarzschild black hole with global monopole charge by relaxing asymptotic flatness and investigated several astrophysical aspects [17]. However, in the presence of the cosmological constant, the metric coefficients of this geometry become modify as follows [18]:…”
Section: Spherically Symmetric Metrics With Horizonsmentioning
confidence: 99%
“…zero external charges and zero cosmological constant) and find the energy-momentum components. This reveals that the non-zero components are T t t = T r r = − 1 2r 2 , which identifies a global monopole [7][8][9][10][11]. The solution (30) can therefore be interpreted as an Einstein-Maxwell plus a global monopole solution in f (R) gravity.…”
Section: F (R) Gravity Coupled With Maxwell Fieldmentioning
confidence: 99%
“…The area of a sphere of radius r (for q 2 = R 0 = 0) is not 4πr 2 but 2πr 2 . Further, it can be shown easily that the surface θ = π 2 has the geometry of a cone with a deficit angle Δ = π 2 [7][8][9][10][11]. It can also be anticipated that a global monopole modifies perihelion of circular orbits, light bending and other physical properties.…”
Section: F (R) Gravity Coupled With Maxwell Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that we could have acceleration non-zero with space part of the metric being flat. It can be shown that non-linear feature of gravitation (field being its own source) goes into curving the space part of the metric, which survives even when potential is constant but not zero [12][13][14]. This is how constant potential in GR gives rise to curved spacetime.…”
mentioning
confidence: 99%